Numerical modelling of bonded and unbonded flax fiber reinforced elastomeric isolator and their application to RC building. (2021) - Sistla, Saiteja; Mohan, S.C.
Abstract: Earthquakes are natural disasters causing havoc to life and property since several centuries. Indian subcontinent has a history of devastating earthquakes in its recent past. One way to tackle an earthquake is to equip the building with a proper seismic resistant system. One of the most popular and effective technique for low and midrise buildings is base isolation. However, existing base isolation systems are very expensive for non-commercial buildings. Hence, this study mainly concentrates on fibre reinforced elastomeric isolators which are cost efficient without a marginal compromise in its performance. A comparison between the performance of unbonded and bonded fibre reinforced elastomeric isolators has been carried out. The unbonded fibre reinforced elastomeric isolators have better performance in terms of stresses, horizontal flexibility, and damping. A low rise reinforced concrete residential building's response is studied with and without fibre reinforced elastomeric isolators. The results show significant reduction in storey drift, story shear, storey level acceleration in both equivalent static method and time history analysis, along with increase in the time period of building's fundamental mode.